Taurine represses oxidative stress in the liver and kidney following exposure to atrazine in Wistar rats - Kayode Afolabi, Olusegun; Teslim Folarin, Dasola; Olusola Aderibigbe, Felix; Arinola, Abimbola (International Journal of Biological Research, 2019)
Background: Taurine is a conditional essential nutrient in man, with proven antioxidant property. This study was designed to evaluate the protective effects of taurine against atrazine (ATZ)-induced hepatic and renal oxidative toxicity in rats.Methods: Wistar rats were orally exposed to ATZ (1/10 LD50) alone or in combination with taurine at 1.5% w/v and 3% w/v in their drinking water for 30 days. After treatment, the liver and kidney were excised for biochemical assays by spectrophotometric methods.Results: Exposure to ATZ significantly elevated hepatic and renal malondialdehyde (MDA) levels when compared to control (p < 0.05). Advanced oxidized protein products (AOPP) were equally increased in these tissues on exposure to ATZ. In addition, reduced glutathione (GSH) and total antioxidant capacity (TAC) were markedly depleted in both organs on exposure to ATZ. Furthermore, activities of the antioxidant enzymes, superoxide dismutase (SOD) and catalase (CAT) were inhibited by ATZ compared to the control. However, co-treatment with taurine attenuated the oxidative responses generated by ATZ exposure in the rats, with the high dose of the amino acid normalizing most of the toxic effects.Conclusion: The study suggested that taurine can protect against ATZ-induced oxidative stress.Â Â Â
Keywords: Antioxidant; Atrazine; Oxidative stress; Pesticide; Taurine.